2009 Fourth International Conference on Risks and Security of Internet and Systems (CRiSIS 2009) 2009
DOI: 10.1109/crisis.2009.5411973
|View full text |Cite
|
Sign up to set email alerts
|

A reference model for risk-aware business process management

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The research identified some steps for linking risk and process management in order to create the roadmap. While the research, in [8], aimed to propose a reference model to enable the modeling of risk aspects for providing the foundation of risk-aware business process simulations.…”
Section: Related Researchmentioning
confidence: 99%
“…The research identified some steps for linking risk and process management in order to create the roadmap. While the research, in [8], aimed to propose a reference model to enable the modeling of risk aspects for providing the foundation of risk-aware business process simulations.…”
Section: Related Researchmentioning
confidence: 99%
“…While it can be said that the scope of ISM is turning towards BPs security, BPM and ISM remain two different disciplines and are most of the time regarded as separate activities [11]. However, the disciplines mutually affect each other's objectives, e.g.…”
Section: A Problem Descriptionmentioning
confidence: 99%
“…Jakoubi and Tjoa [11] introduce a reference model for considering information within the BPM and RM domains. The authors argue for a stronger interweaving between RM and BPM, and present an approach for reengineering business processes as risk-aware.…”
Section: Related Workmentioning
confidence: 99%
“…13 gives a conceptual overview about our approach which serves as basis for two demonstrative service level analysis scenarios within the company ACME: (1) A threat (T1) endangers the assigned resource and (2) the outage of the underpinning contract (UC) shall be evaluated in the course of a Fig. 12 Reference Model applied on the Business Process Elements Activity, Resource Requirement and Resource [18] what-if simulation. In scenario 1, a threat puts an assigned resource (R) in danger.…”
Section: Application Scenariosmentioning
confidence: 99%
“…Fig. 11 Minimal Set of Business Process Elements [18] • A Start is the beginning of a Business Process. There can only be one Start element.…”
Section: A Reference Model For Risk-aware Business Process Managementmentioning
confidence: 99%